The Impact of Anemia on Academic Indicator in Nursing Students: Intelligence Quotient, Academic Potential, Study Concentration and Academic Performance - Santosa, Agus; Fajri, Rizqi Nur; Ramadani, Krisma Novi; Azzahra, Annisa (Proceedings Series on Health & Medical Sciences, 2025)
Anemia, particularly iron deficiency anemia, is a common health issue among nursing students that can significantly impact their academic performance. Purpose: This study aimed to investigate the prevalence of anemia and its effect on key academic indicators, including Intelligence Quotient (IQ), Academic Potential Test (APT) scores, study concentration, and cumulative Grade Point Average (GPA). This study employed a cross-sectional design. A total of 192 nursing students were selected as participants. Anemia status was assessed through blood tests, with participants classified as non-anemic, mildly anemic, or moderately anemic based on hemoglobin levels. Cognitive function was evaluated using standardized measures of IQ and APT scores. Study concentration was assessed through self-reported questionnaires, while academic performance was measured using the students' cumulative GPA. The chi-square test was used to examine the relationship between anemia status and various academic performance indicators. Students with anemia exhibited lower APT scores, reduced study concentration, and poorer GPA outcomes compared to their non-anemic peers (p<0.001). However, the relationship between anemia and IQ was not statistically significant (p<0.05).Conclusion: Anemia negatively impacts cognitive function and academic performance.